Tinjauan Sistem Hukum dalam Penerapan Peraturan Daerah (Perda) Syari’ah di Tasikmalaya - Darnela, Lindra (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
Tasikmalaya is an area that strives to formalize the  Shari'ah in  the  form  of  regional  regulation.  Some  rules  are  made  in order  to support  such  efforts.  In  looking  at  the  effectiveness  of  the enforcement of the law, the legal system is used as a perspective in this study.  The  paper  looked  at  the  implementation  of  the  Regional Regulation  Sya'riat  Islam  in  the  three  elements  of  the  legal  system. Based on the substance of the law, there are several provisions of the regulations that contain bias and allow violence against minorities, such as  the  word  Muslim  and  misleading.  In  terms  of  legal  structure, authorities in charge of ensure the entry into force of these regulations, do not seem to serious in performing their duties. Whereas in the case of the legal culture of society Tasikmalaya provide enormous support in the implementation of the Regulation of Islamic Shari'ah. However this issue is reaping the pros and cons.